PENGARUH SEGITIGA KECURANGAN, RED FLAGS, SKEPTISME PROFESIONAL AUDITOR DAN INDEPENDENSI TERHADAP PENDETEKSIAN KECURANGAN (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI KOTA PEKANBARU DAN KOTA PADANG) - Afifah Izzatil; Hardi Hardi; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the influence of fraud triangle, red flags,auditor professional skepticism and independence on fraud detection. Data usedin this study is primary data (using questionnaire) and data collection tecniquesused is nonprobability sampling. Questionnaire were spread to auditors who workin Public Accounting Firm located in Pekanbaru and Padang. Using warp PLS5.0, the result of this research shows that all independent variables (fraudtriangle, red flags, auditor professional skepticism and independence) influencedependent variable (fraud detection). The value of R square 0,778, which mean78% of independent variables in this research was able to influence dependentvariable, while the remaining 22% is explained by other variables not included inthis study.Keywords : Fraud Triangle, Red Flags, Auditor Professional Skepticism,Independence, Fraud Detection